Diagnostic utility of DNA methylation episignature analysis for early diagnosis of KMT2B-related disorders: case report - Bouhamdani, Nadia; McConkey, Haley; Leblanc, Amélie; Sadikovic, Bekim; Amor, Mouna Ben (Frontiers in Genetics, 2024)
The lysine methyltransferase 2B (KMT2B) gene product is important for epigenetic modifications associated with active gene transcription in normal development and in maintaining proper neural function. Pathogenic variants in KMT2B have been associated with childhood-onset Dystonia-28 and Intellectual developmental disorder, autosomal dominant 68 (MRD 68) for cases of neurodevelopmental impairment without dystonia (DYT28; OMIM 617284 and MRD658; OMIM 619934, respectively). Since its first description in 2016, approximately one hundred KMT2B genetic variants have been reported with heterogeneous phenotypes, including atypical patterns of dystonia evolution and non-dystonic neurodevelopmental phenotypes. KMT2B-related disorders share many Ooverlapping phenotypic characteristics with other neurodevelopmental disorders, as well asand delayed, dystonia, that can appear later in childhood , often delayingoften delays a clinical diagnosis and conventional genetic testing may not provide additional information (e.g., gene panel selection based on early clinical presentation or variants of uncertain significance), which prevents patients and families from obtaining early access to treatments and support. Herein, we describe the early diagnosis of KMT2B-related neurodevelopmental disorderDystonia by DNA methylation episignature testing in a 4-year-old patient without features of dystonia at diagnosis, which canis reported develop present in more than 80% of KMT2B-related disorder cases. before the onset of dystonic features. The proband, a 4-year-old female of Jewish-Israeli descent, presented with speech delay, microcephaly, poor weight gain, attention-deficit and hyperactivity disorder, dysmorphism, intellectual disabilities and joint hyperlaxity, but presented no signs of dystonia at initial evaluation. Episignature screening in this presymptomatic patient enabled accurate genetic diagnosis and timely and actionable intervention earlier in the natural history of Childhood-onset Dystonia-28.